The carbon debt owed to the Earth: are the concept of carbon debt and the attribution of legal personhood for the planet Earth viable legal strategies to boost the carbon credit markets? (2023)
Dissertação (mestrado em Legal Research and Writing Skills) - London School of Economics and Political Science (LSE), Londres, 2023